MANIFESTASI TINGKAT KESADARAN MANUSIA DALAM ANIMASI 3 DIMENSI - Carlos Siagian, Fransiscus; Endriawan, Didit; Rachmawati, Ranti (Telkom University, 2024)
This final project report discusses an animated artwork that combines theconcept of surrealism with the theories of Sigmund Freud and Carl Jung. The purpose of this final project is to explore the complexity of human consciousness and reveal itsmanifestation through symbols that represent Freud's concepts. The medium used in this work is three-dimensional animation with a duration of 3 minutes and an aspect ratio of16:9. Through this work, the author hopes to visualize a unique narrative that triggers audience introspection about the level of human consciousness. The conclusion of this finalproject is that the merging of art and psychology can deepen the understanding of human consciousness and bring innovation in expressing abstract ideas through a strong andcaptivating visual medium. It is hoped that this work can provide new insights into the relationship between art, psychology, and human spirituality, and inspire furtherexploration in understanding the deepest layers of the human mind through the medium of interesting and informative art. Keywords: animation, level of human consciousness, psychoanalysis, surrealism.